Monomethylarsonous acid binds to Cys-104α and Cys-112β of hemoglobin in acute promyelocytic leukemia patients treated with arsenic trioxide. (1st May 2023) - Gao, Chunlu; Lin, Liwang; Li, Jing; Wu, Mengliang; Lv, Jian; Tian, Shuo; Hai, Xin
Abstract: Arsenic trioxide (As2 O3 ) has prominent effect in treating acute promyelocytic leukemia (APL). Identification of arsenic-binding proteins has gained attention for their important biological functions. However, none has been published concerning the binding mechanism of arsenic with hemoglobin (Hb) in APL patients after treatment of As2 O3 . The present study discloses the binding sites of arsenic on Hb in APL patients. Concentrations of inorganic arsenic (iAs), monomethyl arsenic (MMA), and dimethyl arsenic (DMA) in erythrocytes of APL patients were quantified using HPLC-inductively coupled plasma-mass spectroscopy (HPLC-ICP-MS). Hb-bound arsenic was identified by size-exclusion chromatography ICP-MS. The binding sites of arsenic on Hb were determined by mass spectrometry (MS). The concentration trend of arsenic species in erythrocytes of 9 APL patients treated with As2 O3 was iAs>MMA>DMA, and MMA was the predominant methylated arsenic metabolite. Size-exclusion chromatography separation of free and protein-bound arsenic by simultaneous monitoring of 57 Fe and 75 As demonstrated the presence of Hb-bound arsenic. MS information suggested monomethylarsonous (MMA III ) was the dominant arsenic bound to Hb, and further identified that Cys-104α and Cys-112β were two binding sites of MMA III in Hb. MMA III binding to Cys-104α and Cys-112β was responsible for arsenic accumulation in erythrocytes of APL patients. This interaction may contribute to understand the therapeutic effect of As2 O3 as an anticancer drug and its toxicity on APL patients. Highlights: MMA III is the most abundantly bound arsenic species in erythrocytes of APL patients treated with As2 O3 . Cys-104α and Cys-112β is two reactive binding sites of MMA III in hemoglobin. No evidence indicates DMA III binds with cysteines in hemoglobin, probably due to the saturation of binding sites.